Climate-Smart Agriculture in Indonesia - Savelli, Adam; Atieno, Mary Otieno; Giles, James; Santos, Josh; Leyte, James Elwyn D.; Nguyen, Nam Vu Bao; Koostanto, Haryanti; Sulaeman, Yiyi; Douxchamps, Sabine; Grosjean, Godefroy (2021)
This CSA Country Profile describes the risks posed by climate change to agriculture in Indonesia, discusses the potential of CSA to attenuate those risks, identifies factors that can influence the adoption of CSA practices, and highlights potential entry points for investment in CSA at scale. The report is split into two parts; the National Profile and Provincial Profiles. In the National Profile, agriculture’s relation to economic development, livelihoods, specific social groups, land use, food security, and greenhouse gas emissions are explored, in addition to agricultural production systems critical to national food security and livelihoods. In the Provincial Profiles, qualitative research is employed to delve deeper into farming systems and agricultural value chains across three Indonesian Provinces (East Java, North Sumatra, and Nusa Tenggara Timur).